2014
DOI: 10.1002/srin.201400314
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coke Reactivity on Softening‐Melting Dropping Behavior of Iron‐Bearing Burden

Abstract: The influences of the different reactivity cokes on softening-melting dropping of iron-bearing burden were studied by melting-dropping experiment. The pressure difference and shrinkage rate of burden layer, as well as the burden reduction degree at the same temperature were also analyzed. The results show that the softening and melting starting temperature reduces from 1200 to 1160 8C, and the softening and melting end temperature increases from 1290 to 1320 8C, while the melting ending temperature is unchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Despite the general standard of using low reactivity coke in blast furnaces, in recent years a significant research interest has been shown towards the utilization of highly-reactive coke [36][37][38][39][40]. The interest for using high reactivity coke arises from theoretical considerations, which show that a decrease in the equilibrium temperature between reducing gas and wüstite (Fe 1−x O) in the BF shaft can increase the gas utilization rate (CO 2 /CO-ratio), resulting in lower fuel consumption [38], which would bring significant economic savings.…”
Section: Implications On the Blast Furnace Process And Further Develomentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the general standard of using low reactivity coke in blast furnaces, in recent years a significant research interest has been shown towards the utilization of highly-reactive coke [36][37][38][39][40]. The interest for using high reactivity coke arises from theoretical considerations, which show that a decrease in the equilibrium temperature between reducing gas and wüstite (Fe 1−x O) in the BF shaft can increase the gas utilization rate (CO 2 /CO-ratio), resulting in lower fuel consumption [38], which would bring significant economic savings.…”
Section: Implications On the Blast Furnace Process And Further Develomentioning
confidence: 99%
“…In a Japanese Muroran BF, the use of high-reactivity coke decreased the fuel rate by 10 kg/thm (roughly 2%) [37]. High reactivity coke could also improve the softening and melting properties of iron ore [40].…”
Section: Implications On the Blast Furnace Process And Further Develomentioning
confidence: 99%
“…This can lead to small changes to the gas composition through the reversible water-gas shift reaction (Eq. [1]); however, the feed gas was always kept constant independent of the test temperature.…”
Section: Gas Profilesmentioning
confidence: 99%
“…It also impacts the softening and melting properties of iron ore and permeability resistance of the BF. [1] Coke is gasified in the blast furnace shaft by the so-called solution-loss reactions with CO 2 and H 2 O. Solution-loss reactions in the blast furnace are limited by the partial pressure of oxygen in the gas, which is increased as a result of the iron ore reduction reactions in the shaft. It has been said that the total amount of coke solution loss is largely independent of coke reactivity [2,3] and is generally reported to vary between 25 and 30 pct depending on operating conditions.…”
mentioning
confidence: 99%
“…The concept of active nut coke and passive regular coke usage in blast furnace has been introduced in recent past. [22][23][24][25][26][27][28] The reactivity of nut coke is enhanced for its preferential dissolution in the mixed burden layer. The reactivity of nut coke can be enhanced by the addition of Fe 2 O 3 , Fe 3 O 4 and CaO as a dopant.…”
Section: Nut Coke Reactivitymentioning
confidence: 99%